Reinterpreting Non-Muslim Leadership in Indonesia Through Qur’anic and Gracia’s Framework - Masbur Masbur (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2026)
This article aims to discuss Q.S. Al-Maidah: 51 by using Gracia's function of interpretation, especially on the term election of non-Muslim leaders in Muslim-majority Indonesia, which in recent years has become problematic. In the study of the Qur'an itself, this also raises problems in the interpretation of the Qur'an. Based on this background, this study employs a library research approach. This study reinterprets Q.S. Al-Maidah: 51 using the interpretive function framework proposed by Gracia, in this case Gracia has three functions in his interpretation function, namely historical function, meaning function, and implicative function. This paper shows that the historical function of this verse was revealed in the context when the Prophet and his companions faced the potential for war, then the meaning function is the phrase auliya' in this verse which is interpreted as a close friend, loved one, companion, and helper, not as a leader. Finally, with respect to the implicative function, several implications or moral messages emphasize the importance of maintaining harmony among individuals, especially with non-Muslims, and the election of non-Muslim leaders is allowed on the condition that the prospective leaders uphold the values of Pancasila and do not intend to commit crimes that can damage other religions in Indonesia. Abstrak Artikel ini hendak membahas Q.S. Al-Maidah: 51 dengan menggunakan fungsi interpretasi Gracia, terutama pada term pemilihan pemimpin non-Muslim di Indonesia yang mayoritas beragama Islam, yang beberapa tahun kebelakang sempat menjadi problematik. Dalam pengkajian Alquran sendiri, hal ini turut memunculkan permasalahan dalam interpretasi Alquran. Berdasarkan latar belakang tersebut, tulisan ini akan menggunakan studi kepustakaan (library Research). Penelitian ini hendak mencoba menafsirkan kembali terkait Q.S Al-Maidah: 51 dengan menggunakan pisau analisis fungsi interpretasi yang digagas oleh Gracia, dalam hal ini Gracia mempunyai tiga fungsi dalam fungsi interpretasinya, yaitu historical function, meaning function, dan implicative function. Dari tulisan ini menghasilkan bahwa terkait historical function ayat ini turun dalam konteks ketika Nabi dan para sahabatnya menghadapi potensi perang, kemudian meaning function terdapat frasa auliya’ pada ayat ini yang diartikan sebagai teman dekat, orang yang dicintai, sahabat, dan penolong, bukan sebagai pemimpin, terakhir terkait implicative function terdapat beberapa impikasi atau pesan moral yang mengajarkan kepada manusia untuk selalu menjaga keharmonisan antar sesama terutama dengan umat non-Muslim, dan pemilihan pemimpin non-Muslim satu sisi dibolehkan dengan syarat calon pemimpin tersebut memegang teguh nilai-nilai Pancasila dan tidak berniat melakukan kejahatan yang dapat merusak agama-agama lain yang ada di Indonesia.